ANALISIS YURIDIS DISPARITAS PUTUSAN HAKIM TERHADAP TINDAK PIDANA PENCURIAN DENGAN KEKERASAN YANG MENYEBABKAN MATINYA KORBAN - Julastri, Julastri; Husna, Lenny (LPPM Universitas Putera Batam, 2019)
Indonesia adheres to the concept as a legal state which is clearly stipulated in the 1945 Constitution. Along with this conception, the judiciary exercising judicial power must be firmly holding the principle of rule of law, namely a country that exercises its governmental power based on law. As a legal state, Indonesia adheres to one of the principles, namely the principle of equality before the law. The disparity of gaps in decisions against perpetrators of criminal acts of theft with violence which resulted in the death of the victim by the judge caused injustice both for the defendant and the victim as well as the wider community. In this study the formulation of the problem that the author discusses is what factors cause disparity in the judge's decision and how the disparity of the judge's decision on the crime of theft with violence that causes the death of the victim. From the research, the authors found a variety of arrangements which generally implied the disparity of decisions. The conclusion of this study is that the causes of disparity from two factors are juridical theoretical factors and empirical factors.